The campaign Walking barefoot, we also learn to read: the education project to weed illiteracy of Natal/RN (Research, Society and Development, 2017)
This article aims at studying the education project carried out in Natal/RN at the Campanha de Pé no Chão também se Aprende a Ler (Campaign Walking barefoot, We Also Learn to Read). The study identifies the illiteracy during the historical moment of Djalma Maranhão (1915 – 1971) as Mayor of Natal/RN. He had the purpose of fighting the alarming illiteracy numbers in the capital of Rio Grande do Norte. The research was based on the websites of INEP and IBGE. It, initially, emphasised a quantitative approach. However, after the results, we used a more qualitative approach for the analysis process. Our theoretical basis was on the studies of Moacyr de Góes (1980) and José Willington Germano (1989). The research also revealed that the illiteracy numbers faced in the 60s are still present in the society of Natal. Moreover, the numbers are higher if we consider absolute figures. In Brazil, the amount of illiterates challenges society to wipe out their destructive stains from people’s lives.